Ocular chemical burn associated with gel type alcohol-based hand sanitizer: A case report. Issue 42 (22nd October 2021) - Lee, Jaekyoung; Jun, Jong Hwa
Abstract: Introduction: Alcohol-based hand sanitizers (ABHS) are widely used for hand hygiene due to the coronavirus disease pandemic. However, risk awareness regarding its adverse effects is lacking. We aim to report a case of ocular chemical burn that showed severe clinical presentation associated with ABHS. Patient concerns: A 5-year-old girl presented with severe left eye pain after 62% gel-type ABHS splashed into her eye. Diagnosis: On slit lamp examination, a near total corneal and conjunctival epithelial defect with limbal pale on the lower half of the cornea was noted. Severe ocular burn by ABHS was prominent with suspected limbal stem cell damage. Interventions: She was hospitalized and was prescribed topical medications including antibiotics, steroid eye drops with preservative-free artificial tears, and oral nonsteroidal anti-inflammatory drugs. Outcomes: Despite intensive medical treatments, the corneal and conjunctival epithelial defects showed no improvement up to the 4 th hospital day. After additional instillation of autoserum eye drops to promote epithelial healing, the corneal epithelium barely recovered from the temporal limbus. On the third week of admission, the epithelial defect was completely resolved without corneal opacity, although with minimal symblepharon in the lower fornix. Conclusions: Gel-type ABHS can cause severe form of ocular chemical burn such as delayed ocular surface healing. In clinical setting, immediate and thorough rinsing of alcohol-based gel and early intensive treatment are crucial.